Slowly coming out of COVID-19 restrictions in Australia: Implications for working from home and commuting trips by car and public transport. (October 2020) - Beck, Matthew J.; Hensher, David A.; Wei, Edward
Abstract: With the onset of COVID-19 restrictions and the slow relaxing of many restrictions, it is imperative that we understand what this means for the performance of the transport network. In going from almost no commuting, except for essential workers, to a slow increase in travel activity with working from home (WFH) continuing to be both popular and preferred, this paper draws on two surveys, one in late March at the height of restrictions and one in late May as restrictions are starting to be partially relaxed, to develop models for WFH and weekly one-way commuting travel by car and public transport. We compare the findings as one way to inform us of the extent to which a sample of Australian residents have responded through changes in WFH and commuting. While it is early days to claim any sense of a new stable pattern of commuting activity, this paper sets the context for ongoing monitoring of adjustments in travel activity and WFH, which can inform changes required in the revision of strategic metropolitan transport models as well as more general perspectives on future transport and land use policy and planning. Highlights: Two wave study examining work from home (WFH) and commute behaviour through COVID-19 pandemic. New models for WFH and impact on commuting activity. Evidence of changes WFH and commuting from immediately after restrictions to their initial easing Small decreases in WFH and increases in car-based commuting starting to occur. WFH has been a positive experience and many would to WFH more than before COVID-19, if they have an appropriate space. Policy makers should encourage employer support for working from home and help identify and reduce barriers to doing so.